Embedded generation (EG) allocation using artificial bee colony (ABC) algorithm - Desmond Soon Chan Onn (School of Electrical System Engineering, University Malaysia Perlis, 2011)
This Final Year Project is proposed to study the Artificial Bee Colony (ABC) algorithm in determining the location and sizing of Embedded Generation (EG) in distribution network. The purpose is to minimize total system real power loss and to improve the quality of the overall system network. The ABC algorithm is a new meta-heuristic population-based optimization technique inspired by the intelligent foraging behavior of honeybee swarms. The ABC algorithm has excellent solution quality and convergence characteristic. From the simulations that have been carried out, ABC algorithm gives good optimal results in this EG allocation problem. The ABC program has been developed in MATLAB. In order to complete this project, knowledge about integrating power system engineering and ABC are studied. The IEEE 69-bus system is used to verify the correctness and effectiveness of the developed ABC program.